Prostate stem cell antigen (PSCA): a Jekyll and Hyde molecule? - Saeki, Norihisa (2010)
Prostate stem cell antigen (PSCA) is a glycosylphosphatidylinositol (GPI)-anchored cell surface protein. Although PSCA is thought to be involved in intracellular signaling, much remain unknown regarding its physiological function and regulatory mechanism in normal and cancer cells. It is up-regulated in several major cancers including prostate, bladder and pancreatic cancers. The expression of PSCA is positively correlated with advanced clinical stage and metastasis in prostate cancers and is also associated with malignant progression of pre-malignant prostate lesions. Therefore, PSCA has been proposed as a biomarker of diagnosis and prognosis, as well as a target of therapy for these cancers. In addition, PSCA has also shown clinical potential in immunotherapy as a prostate specific antigen which, when presented by dendritic cells, may elicit strong tumor specific immunity. In contrast, PSCA is down-regulated in esophageal and gastric cancer and may have tumor-suppressing function in the gastric epithelium. Recent exciting findings that genetic variations of PSCA conferred increased risks of gastric cancer and bladder cancer have opened up a new avenue of research regarding the pathological function of PSCA. PSCA appears to be a Jekyll and Hyde molecule that plays differential roles, tumor promoting or suppressing, depending on the cellular context.